Whole‐brain quantitative mapping of metabolites using short echo three‐dimensional proton MRSI. Issue 2 (28th November 2014) - Lecocq, Angèle; Le Fur, Yann; Maudsley, Andrew A.; Le Troter, Arnaud; Sheriff, Sulaiman; Sabati, Mohamad; Donnadieu, Maxime; Confort‐Gouny, Sylviane; Cozzone, Patrick J.; Guye, Maxime; Ranjeva, Jean‐Philippe
<x xml:space="preserve">Abstract</x> Background To improve the extent over which whole brain quantitative three‐dimensional (3D) magnetic resonance spectroscopic imaging (MRSI) maps can be obtained and be used to explore brain metabolism in a population of healthy volunteers. Methods Two short echo time (20 ms) acquisitions of 3D echo planar spectroscopic imaging at two orientations, one in the anterior commissure–posterior commissure (AC‐PC) plane and the second tilted in the AC‐PC +15° plane were obtained at 3 Tesla in a group of 10 healthy volunteers. B1+, B1−, and B0 correction procedures and normalization of metabolite signals with quantitative water proton density measurements were performed. A combination of the two spatially normalized 3D‐MRSI, using a weighted mean based on the pixel wise standard deviation metabolic maps of each orientation obtained from the whole group, provided metabolite maps for each subject allowing regional metabolic profiles of all parcels of the automated anatomical labeling (AAL) atlas to be obtained. Results The combined metabolite maps derived from the two acquisitions reduced the regional intersubject variance. The numbers of AAL regions showing N‐acetyl aspartate (NAA) SD/Mean ratios lower than 30% increased from 17 in the AC‐PC orientation and 41 in the AC‐PC+15° orientation, to a value of 76 regions of 116 for the combined NAA maps. Quantitatively, regional differences in absolute metabolite concentrations (mM) over the whole brain were depicted such as in the GM of frontal lobes (cNAA = 10.03 + 1.71; cCho = 1.78 ± 0.55; cCr = 7.29 ± 1.69; cmIns = 5.30 ± 2.67) and in cerebellum (cNAA = 5.28 ± 1.77; cCho = 1.60 ± 0.41; cCr = 6.95 ± 2.15; cmIns = 3.60 ± 0.74). Conclusion A double‐angulation acquisition enables improved metabolic characterization over a wide volume of the brain. J. Magn. Reson. Imaging 2015;42:280–289.